EDUCATIONAL TRAJECTORY OF KNRTUKAI - Irina S. Khalitova (Высшее образование в России, 2017)
Abstract. The article gives a detailed definition of the notion “extracurricular activity”, considers its types, forms and results. The article examines the role that extracurricular activity plays in the formation of professionally important qualities, general competences of students involved in a process of extracurricular activities.